Increasing Public Knowledge about Vitamin and Health Supplements during the COVID-19 Pandemic - Ulya Safrina; Khairun Nida; Surahman Surahman (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Vaccine development and enhancing the body’s immune system are the focus in dealing with COVID-19. One way to improve the body’s immune system is to consume immunostimulating substances, such as health supplements. However, most people still think that health supplements can be consumed daily without certain restrictions because vitamins are not considered drugs. The purpose of implementing this activity is to increase knowledge about how to use vitamins and health supplements and improve community skills to identify natural or fake vitamins and health supplements. The targets of this community service activity were cadre mothers from all sub-district in Utan Kayu Utara Village. The method of implementing the activity is by direct education and giving leaflets. Community service activities in the Utan Kayu Utara sub-district ran smoothly. Participants were very enthusiastic about asking and discussing the material presented. The number of participants in the activity was 40 people. There was an increase in the average value of knowledge from 59.00 ± 11.0 to 86.50 ± 7.49 after providing education through counselling and media leaflets.